Formulation and Clinical Evaluation of Orphenadrine citrate as a Plain Tablet - Karim F. Jumaa, Abdul; A.Abdulrasool, Alaa; A.Al â€“ Dujali, Hikmet (Iraqi Journal of Pharmaceutical Sciences, 2017)
Orphenadrine is an anticholinergic ,antimuscarinic , centrally acting skeletal muscle relaxant .It presents in the form of citrate and HCl salts which are used in treatment of the symptoms of mild Parkinson’s disease and also it is used as adjuvant with other drugs in the therapy . Many trials were made to formulate Orphenadrine citrate as a plain tablet using wet granulation or direct compression technique in order to get a satisfactory formula through studying the effect of various factors such as binders , diluents and disintegrants types . The best formula was obtained by using Poly Vinyl Pyrolidine (PVP) as a binder also the results indicated that starch and mannitol gave acceptable physical properties to the tablets when they were used as diluents . At the same time , the results showed that Avicel which was used as a disintegrant gave an acceptable disintegration and dissolution time in comparison with the reference tablet DISIPAL Ã’. In addition , the selected formula was used to study the effect of method of incorporation of disintegrant on the physical properties of tablets .It was found that the intragranular incorporation resulted in a shorter disintegration and dissolution times .The stability of Orphenadrine citrate prepared tablets was also studied upon storage at 50Â°C, 60Â°C and 70Â°C for four months .The drug was fairly stable and the expiration date for the prepared tablet was considered to be equal for 5 years .On the other hand , the results of clinical study on patients suffering from Parkinson’s disease indicated that patients with tremor (regular rhythmic oscillation of extremities especially hand and finger ) and mild symptoms of Parkinson’s disease showed a good response to the prepared tablets , but it had no effect on patients of dystonia ( fixed upward gaze , neck twisting ,clenching jaws ) and akinesia ( slow down of movement of voluntary muscle and difficulty of initiation of movement ). The overall results of this study indicate that the drug can be prepared as tablets , which fit the requirements of British Pharmacopoeia since the prepared tablets gave satisfactory results .